PENERAPAN PRINSIP-PRINSIP FIQIH MUAMALAH PADA PLATFORM SHOPEE - Zahrotul T, Annisa Ica; Faitullani, Rizka; Putri, Sinta Retno; Radhiyah, Nafi’ah Alya; Firdasari, Rohida; Waluyo, Waluyo (Cahaya Ilmu Bangsa, 2024)
The widespread use of online shopping in this digital age has become an easy solution widely adopted by society. However, the implementation of the sistems used within it raises doubts regarding its alignment with Islamic principles. The purpose of this research is to examine the application of Muamalah Fiqih or Islamic law in the online shopping platform Shopee. This study is conducted to ensure the compatibility of Shopee's sistem with Muamalah Fiqih. The method used in this research is qualitative, with a literature review approach. The data used in this study is gathered from various sources, including books, journals, and articles. The results of this study indicate that Shopee's sistem is in accordance with Sharia law or Fiqih. Every sistem applied in Shopee, from transaction methods to payment gateways, is in line with the existing Fiqih regulations. This includes the absence of elements such as riba (usury), gharar (ambiguity), and maysir (gambling), which are prohibited in Islam. Shopee ensures that every transaction is carried out transparently, fairly, and with mutual consent, fulfilling the principles of halal transactions as guided by Islamic teachings. Hence, the Shopee platform can be considered a Sharia-compliant e-commerce sistem.